Stearidonic acid combined with alpha-linolenic acid improves lipemic and neurological markers in a rat model subject to a hypercaloric diet. (August 2018) - Cardoso, Carlos; Martinho, Joana Paiva; Lopes, Paula A.; Martins, Susana; Correia, Jorge; Afonso, Cláudia; Alarcón, Francisco J.; González-Fernández, María J.; Pinto, Rui M.; Prates, José A.; Bandarra, Narcisa M.; Guil-Guerrero, José L.
Highlights: ALA & SDA reduced lipids, VLDL-cholesterol, & triacylglycerols in LIN & BUG groups. CREB gene levels were enhanced by ALA-, (SDA + ALA)-, & (EPA and DHA)-rich diets. ALA, SDA + ALA, & EPA + DHA sources counteract the health effects of hypercaloric diets. Summary: In this study, we hypothesized that terrestrial plant oils, rich in alpha linolenic acid (ALA) and stearidonic acid (SDA) relative to fish oil, rich in eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), prevent negative effects on cardiovascular and neurological function using a rat model fed a hypercaloric diet. Results showed effects on the FA profile, namely, eicosapentaenoic, EPA, and docosahexaenoic, DHA, levels. There were also effects on neural aspects (cAMP response element-binding protein, CREB, gene expression, at least, doubled) and the pro-inflammatory/anti-inflammatory balance (TNF-α, tumor necrosis factor alpha reduced by 30–50%). The most positive impact of ALA and SDA was the beneficial reduction of total lipids (from 395 ± 3 to 352–361 mg/dL), VLDL-cholesterol (from 21.8 ± 0.2 to 14.1–17.8 mg/dL), and triacylglycerols (from 109 ± 1 to 71–89 mg/dL) in both LIN (diet enriched in linseed oil) and BUG (diet enriched in Buglossoides oil) groups. Overall, data indicate that ALA- and SDA-rich lipid sources may counteract the undesirable cardiovascular effects of a hypercaloric diet based on milk fat.